La prueba científica - Simons Pino, Adrián (2017)
The scientific advances have greatly influenced the perception of the facts, generating some objectivation of the perception of the proof . In the past, many decisions were made on the basis of common sense and presumptions. This is reduced by the performance of more reliable evidence, which can generate a better conviction in the judge or legal operator.In this article, the author develops the effects that scientific evidence has had on legal practitioners, such as judges. Also, a theoretical framework will be proposed to understand this type of test, taking as reference emblematic cases.